(untitled) (Prosiding Konseling Kearifan Nusantara (KKN), 2025)
This research discusses the integration of Javanese and Papuan local wisdom in guidance and counseling (BK) services at SMA Negeri 6 Kediri, with the aim of building students’ multicultural character and nationalism. Based on observations and interviews, it was found that despite the initial assumption that Javanese and Papuan students do not mix well, the interaction between them is quite harmonious. The use of local wisdom values, such as politeness and tolerance from Javanese culture, as well as togetherness and solidarity from Papuan culture, can strengthen students’ social relationships and communication ethics. The special attention given to Papuan students, who are away from their families, also has a positive impact on their learning motivation, although stricter supervision in the dormitories is needed. The integration of such values in BK services can strengthen the sense of nationalism and create an inclusive school environment. Therefore, it is important to design counseling programs that integrate local wisdom and pay attention to students’ cultural diversity to create a more tolerant and nationalistic generation.